ЮҚОРИ МАЛАКАЛИ ФУТБОЛЧИЛАРНИНГ МУСОБАҚА ДАВРИ ЎЙИНЛАРАРО ЦИКЛЛАРИ УЧУН МАШҒУЛОТ ДАСТУРЛАРИНИ ИШЛАБ ЧИҚИШДА ЗАМОНАВИЙ ЁНДАШУВЛАР - Комилов, Ж.; Сарибоев, Ш.; Каримов, Ф. (SCIENCE and SOCIETY, 2020)
This article deals with the problem of developing training programs for the intermediate cycle, based on the analysis of training and competitive activities of senior players. Scientific and methodological problems of planning and managing the process of training highly qualified players in Intercollegiate cycles are based on research by leading experts, such as R.A. Akramov (2005), M.A.Godik (2007), Sh.T. Iseev (2017), R.I.Nurimov (2005), A.I. Tolibjanov (2012), in the planning process of highly qualified players. The methodology and tools for planning high-level players ' training sessions for high-profile inter-cycles are based on many years of experience in sports theory and summarizing the results of national teams and monitoring the competitiveness of leading teams. The analysis of indicators of physical fitness, technical, tactical efficiency of national teams and leading teams participating in national Championships is also presented. Based on the analysis of modern football trends, there are ways to improve the physical qualities of highly qualified players and improve the effectiveness of their technical and tactical actions in inter-cycle competitions. And also, the approximate planning of the workload for the intermediate cycles of the competition is presented.
Keywords: highly qualified players; competitive activity; training; physical activity; micro cycle; technical and tactical movements; physical training; sport uniform; pedagogical control